2002
DOI: 10.1046/j.1351-0754.2002.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the chemical composition of soil organic matter after application of compost

Abstract: Summary Is the composition of soil organic matter changed by adding compost? To find out we incubated biowaste composts with agricultural soils and a humus‐free mineral substrate at 5°C and 14°C for 18 months and examined the products. Organic matter composition was characterized by CuO oxidation of lignin, hydrolysis of cellulosic and non‐cellulosic polysaccharides (CPS and NCPS) and 13C cross‐polarization magic angle spinning nuclear magnetic resonance (CPMAS 13C‐NMR) spectroscopy. The lignin contents in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 30 publications
9
45
1
2
Order By: Relevance
“…Reduction in pH due to higher levels of biosolid addition could be ascribed to increased mineralisation of organic matter coupled with oxidation of N and S. In addition, it could be also attributed to the reduced concentration of HCO 3 − and CO 3 2− ions in solution (Brofas et al 2000;Courtney et al 2003;Xenidis and Harokopou 2005). More than a two-fold increase in C content due to compost addition was observed in the current study and similar results reported by various researchers (Leifeld et al 2002;Weber et al 2007). Commercial compost at 50 t ha -1 produced highest organic C (0.96%) followed by biosolid mix (0.75%) and piggery mix (0.64%).…”
Section: Composts Effects On Zn Formssupporting
confidence: 90%
“…Reduction in pH due to higher levels of biosolid addition could be ascribed to increased mineralisation of organic matter coupled with oxidation of N and S. In addition, it could be also attributed to the reduced concentration of HCO 3 − and CO 3 2− ions in solution (Brofas et al 2000;Courtney et al 2003;Xenidis and Harokopou 2005). More than a two-fold increase in C content due to compost addition was observed in the current study and similar results reported by various researchers (Leifeld et al 2002;Weber et al 2007). Commercial compost at 50 t ha -1 produced highest organic C (0.96%) followed by biosolid mix (0.75%) and piggery mix (0.64%).…”
Section: Composts Effects On Zn Formssupporting
confidence: 90%
“…CO 2 evolved during the incubation was trapped in 1 M NaOH, the excess of which was then titrated with 0.1 M HCl after addition of BaCl 2 . Mineralized C was calculated as the CO 2 efflux rate (mg C g À1 soil day À1 ) and cumulative CO 2 -efflux (g kg À1 soil) according to Usman et al (2004) and Leifeld et al (2002). Soil labile C fraction was measured after extraction using 0.5 M K 2 SO 4 solution and oxidation with K 2 Cr 2 O 7 at 100°C and a subsequent back-titration of the unreduced dichromate (Vance et al, 1987).…”
Section: Incubation Experimentsmentioning
confidence: 99%
“…The diverse nature of the relationship between compost and plant health includes inactivation of pathogens during the process of composting (Bollen 1993), indirect antiphytopathogenic influence of compost due to modified plant growth conditions (Delschen 1999;Leifeld et al 2002) and direct suppression of plant pathogens (Hoitink et al 1997(Hoitink et al , 2001. A complex interaction between abiotic characteristics and microbial activity is proposed to be responsible for suppressive properties of certain substrates (Alabouvette 1986), though the exact mechanisms of action are still widely unknown.…”
Section: Introductionmentioning
confidence: 99%